ANALISIS KOHESI DAN KOHERENSI WACANA LISAN KAJIAN NASKAH PEMENTASAN WAYANG KULIT SASAK - Murtafi’ah, Wahidatul; Hendri (LPPM Institut Pendidikan Nusantara Global, 2022)
Language is a tool for communication in the life of human beings to be able to interact properly. Besides Indonesian as the national language, in Indonesia there are also regional languages ​​depending tribal regions, such as the Minangkabau language. Minangkabau language has dialects vary widely, one of them languages ​​Minangkabau in South Solok regency. This study discusses the reduplication in Minangkabau language in South Solok regency. The research is a qualitative research with descriptive method. The research data used linguistic form of data derived from primary and secondary sources. Reduplications discussed in this study was the shape and meaning of Minangkabau language reduplication in South Solok regency. First, the reduplicated form found in Minangkabau language in South Solok district can be grouped into three, namely (1) the form of the noun reduplication, (2) reduplication of verbs, and (3) adjective reduplication. Second, the meaning of reduplication found in Minangkabau language in South Solok regency there are three, namely (1) the meaning of the noun reduplication, (2) reduplication of verbs, and (3) adjective reduplication. Reduplicated form is divided into two: (1) the form of reduplicated root and (2) form the basis affixed reduplication. .